STATE OF HOUSE BASIC SANITATION IN 3 RT KEDUNG BANTENG VILLAGE VULNERABLE AREAS TANGGLANGIN DISTRICT, SIDOARJO - Alya, Safira Alya Nurul Jannah; Kriswandana, Ferry; Rustanti, Iva (Jurnal Higiene Sanitasi, 2021)
Based on data from the Technical Implementation Unit (UPT) the Tanggulangin Health Center in 2020, there were 123 diarrhea cases.The high cases of diarrhea are due to several poor sanitation conditions that have a negative impact on aspects of lie. Such as environmental pollution tat causes environmental-based diseases. This study aims to determine the description of basic house sanitation in 3 flood-prone areas, Kedung Banteng Village, Tanggulangin District, Sidoarjo.. The method used is descriptive method. The sampling technique used was simple random sampling with a sample 57 ouses based on house populations and 15 samples of clean water to be tested in the laboratory. The data collection technique is primary data collection through observation sheets and laboratory examination results regarding the bacteriological quality of clean water. The results showed that the sanitation condition in the 3 RT flood-prone areas, including clean water supply got a score of 89% in te good category. The latrine facilities, got a score of 100% in the good category. The trash can facilities, got a score of 64%, 66% and 45% in the sufficient category. SPAL , get a score of 40% in the sufficient category. The Drainage facilities, get a score of 50% in the sufficient category. Te results of bacteriological quality inspection on 100% clean water do not meet health requirement. The Conslusion of the study in the three areas of Kedung Banteng Village on basic house sanitation there are two facilities with good ratings and three other facilities getting adequate score. It is recommended for Health agencies to provide education about the importance of basic home sanitation facilities and the community maintain cleanliness to prevent environmental-based diseases.